Peritransplant eculizumab does not prevent delayed graft function in deceased donor kidney transplant recipients: Results of two randomized controlled pilot trials. Issue 2 (8th October 2019) - Schröppel, Bernd; Akalin, Enver; Baweja, Mukta; Bloom, Roy D.; Florman, Sander; Goldstein, Michael; Haydel, Brandy; Hricik, Donald E.; Kulkarni, Sanjay; Levine, Matthew; Mehrotra, Anita; Patel, Anup; et al.
Abstract : Animal models and observational human data indicate that complement, including C5a, pathogenically participates in ischemia reperfusion (IR) injury that manifests as delayed graft function (DGF) following deceased donor kidney transplantation. We report on the safety/efficacy of anti‐C5 monoclonal antibody eculizumab (Ecu) administered in the operating room prior to reperfusion, to prevent DGF in recipients of deceased donor kidney transplants in two related, investigator‐sponsored, randomized controlled trials. Eight recipients from a single center were enrolled in a pilot study that led to a 19‐subject multicenter trial. Together, 27 deceased donor kidney transplant recipients, 16 Ecu‐treated and 11 controls, were treated with rabbit antithymocyte globulin, tacrolimus, mycophenolate mofetil with or without glucocorticoids, and followed for 6 months. Data analysis showed no epidemiological or transplant‐related differences between study arms. Ecu was well tolerated with a similar severe adverse event incidence between groups. The DGF rate did not differ between Ecu‐treated (44%) and control (45%, P  = 1.0) subjects. Serum creatinine reduction in the first week after transplantation, and graft function up to 180‐days post‐transplant, were also similar. Ecu administration was safe but did not reduce the rate of DGF in a high‐risk population of deceased donor recipients. Abstract : The results of two randomized controlled pilot trials show no efficacy for peritransplant administration of eculizumab in preventing delayed graft function following deceased donor kidney transplantation.